Common variant of BCAS3 is associated with gout risk in Japanese population: the first replication study after gout GWAS in Han Chinese - Masayuki Sakiyama; Hirotaka Matsuo; Hirofumi Nakaoka; Yusuke Kawamura; Makoto Kawaguchi; Toshihide Higashino; Akiyoshi Nakayama; Airi Akashi; Jun Ueyama; Takaaki Kondo; Kenji Wakai; Yutaka Sakurai; et al. (BMC, 2018)
Abstract Background Gout is a common disease resulting from hyperuricemia which causes acute arthritis. A recent genome-wide association study (GWAS) of gout identified three new loci for gout in Han Chinese: regulatory factor X3 (RFX3), potassium voltage-gated channel subfamily Q member 1 (KCNQ1), and breast carcinoma amplified sequence 3 (BCAS3). The lack of any replication studies of these three loci using other population groups prompted us to perform a replication study with Japanese clinically defined gout cases and controls. Methods We genotyped the variants of RFX3 (rs12236871), KCNQ1 (rs179785) and BCAS3 (rs11653176) in 723 Japanese clinically defined gout cases and 913 controls by TaqMan method. rs179785 of KCNQ1 is also evaluated by direct sequencing because of difficulties of its genotyping by TaqMan method. Results Although the variants of RFX3 and BCAS3 were clearly genotyped by TaqMan method, rs179785 of KCNQ1 was not, because rs179785 (A/G) of KCNQ1 is located at the last nucleotide ("A") of the 12-bp deletion variant (rs200562977) of KCNQ1. Therefore, rs179785 and rs200562977 of KCNQ1 were genotyped by direct sequencing in all samples. Moreover, by direct sequencing with the same primers, we were able to evaluate the genotypes of rs179784 of KCNQ1 which shows strong linkage disequilibrium with rs179785 (D' = 1.0 and r 2  = 0.99). rs11653176, a common variant of BCAS3, showed a significant association with gout (P = 1.66 × 10− 3; odds ratio [OR] = 0.80); the direction of effect was the same as that seen in the previous Han Chinese GWAS. Two variants of KCNQ1 (rs179785 and rs179784) had a nominally significant association (P = 0.043 and 0.044; OR = 0.85 and 0.86, respectively), but did not pass the significance threshold for multiple hypothesis testing using the Bonferroni correction. On the other hand, rs200562977 of KCNQ1 and rs12236871 of RFX3 did not show any significant association with gout. Conclusion BCAS3 is a coactivator of estrogen receptor alpha, and the influence of estrogen to serum uric acid level is well known. Our present replication study, as did the previous gout GWAS, demonstrated the common variant of BCAS3 to be associated with gout susceptibility.